International Currency in Support Global Economic Growth - Selfia Putri Johana Eka Ningsih Simatupang; Lola Irmayunda; Isyahruna Primadani; Dwita Sakuntala (SEAN Institute, 2025)
This article explore role strategic international currency in support growth global economy, with focus on stability economy, investment cross- country, and trade international. Research This use approach qualitative through analysis literature For identify How currencies such as US dollar, euro and Chinese yuan influence dynamics global economy. Research results show that stability mark international currency No only increase market confidence but also facilitate more transactions efficient. In addition, the transformation digitalization currency and effort dedollarization add complexity in use international currency. Findings This expected give outlook for maker policies and market players to utilise potential international currency in create system more finances inclusive and sustainable.